Clinical and Biochemical Characteristics in PCOS Women With Menstrual Abnormalities - Vasiliki Christodoulopoulou; Eftihios Trakakis; Vasilios Pergialiotis; Melpomeni Peppa; Charalampos Chrelias; Dimitrios Kassanos; Nikolaos Papantoniou (Tehran University of Medical Sciences, 2017)
Objective: The purpose of the present study was to examine the impact of menstrual cycle abnormalities among patients with polycystic ovary syndrome (PCOS) on biochemical and anthropometric characteristics. Materials and methods: We conducted a prospective observational study of patients 17-35 years of age with PCOS that attended the department of Gynecological Endocrinology of our hospital. Results: A total of 309 women with PCOS participated in the study. In total, 72.2% suffered from menstrual cycle disorders. In our study 15.1% of women were overweight and 24% were obese. Also, 36% of the sample had androgenetic alopecia and 56.4% had acne. According to the stepwise discriminant analysis, we observed that glucose displayed the strongest association to the menstrual status (F to eliminate = 14.13), followed by endometrial thickness (F to eliminate = 10.89), waist circumference (F to eliminate = 10.17), LH levels (F to eliminate = 8.15) and PRL (F to eliminate = 4.45). Significantly higher levels of LH and TSH and lower levels of prolactin were found in women with menstrual disorders compared to those with normal menstrual cycles. Fasting glucose was also considerably higher among these patients although markers of insulin resistance such as the Matsuda, Quicki and HOMA-IR indices did not differ. Conclusion: According to the findings of our study PCOS patients with menstrual disorders exhibit hormonal alterations and elevated fasting glucose. Future studies are needed in this field to corroborate our findings and determine the anthropometric and biochemical profile of patients with menstrual cycle irregularities.